Alelopatia em espécies nativas do Cerrado / Allelopathy in native species of brazilian Savannah - Marchi, Edilene Carvalho Santos; Marchi, Giuliano; Sousa-Silva, José Carlos; Ikeda, Fernanda Satie; Fagg, Christopher William (Savannah Journal of Research and Development, 2017)
In this review, allelopathic studies of 70 species native from Cerrado, distributed in 34 families and studied from 1992 until late 2008, were compiled in a list. The Cerrado Biome comprises several distinct landscape areas constituted by different phytophysiognomies, and is the most biodiverse savanna in the world. From the 12.000 species native to Cerrado, only a small amount of species have been studied. Few allelochemicals in leaves, flowers, shoots, and subterranean parts of plant species were identified in the restricted data. Isolated compounds from a few plants were shown in detail. The synthesis of those compounds was not identified for use in comprehensive control of plants and other organisms. Future studies should be directed to unknown and better known plants; identification of new compounds and their metabolism; synthesis and mode of action of those new compounds; agriculture effects and Cerrado plants establishment. RESUMO Nesta revisão, estudos alelopáticos de 70 espécies nativas do Cerrado, distribuídas em 34 famílias e estudadas de 1992 até 2008 foram compiladas em uma lista. O Bioma Cerrado compreende várias paisagens distintas constituídas por diferentes fitofisionomias e é uma das biodiversidades mais ricas no mundo. Das 12.000 espécies lenhosas nativas do Cerrado, somente em uma pequena parte foram estudadas. Poucos aleloquímicos em folhas, flores, parte aérea e partes subterrâneas de espécies de plantas foram identificadas em dados restritos. Compostos isolados de poucas plantas foram mostrados em detalhes. A síntese desses compostos não foi utilizada para uso em controle de plantas daninhas e outros organismos. Futuros trabalhos poderiam ser direcionados para plantas estudadas e ainda não estudadas; a identificação de novos compostos e seu metabolismo; síntese e modo de ação daqueles compostos; efeitos na agricultura e no estabelecimento de plantas no Cerrado.